Участь прокурора у цивільних справах - Подоляка, Сергій Анатолійович (My University, 2012)
Розглядається процесуальне становище участі прокурора у цивільних справах. Досліджуються форми вступу прокурора у справу. Аналізуються права прокуратури під час представництва законих прав та інтересів громадян під час участі у цивільному процесі. The procedural status of the prosecutor's participation in civil cases is considered. The forms of the prosecutor's entry into the case are studied. The rights of the prosecutor's office when representing the legal rights and interests of citizens during participation in civil proceedings are analyzed.
Keywords: прокурор; public prosecutor; цивільна справа; civil case; цивільний процес; civil process; прокуратура; prosecutor's office